Clinical Parameters in Osteoporosis Patients Supplemented With PMA-Zeolite at the End of 5-Year Double-Blinded Clinical Trial - Kraljević Pavelić, Sandra; Krpan, Dalibor; Žuvić, Marta; Eisenwagen, Sandra; Pavelić, Krešimir (Frontiers in Medicine, 2022)
Osteoporosis is among the most common pathologies. Associated complications in osteoporotic patients, in particular hip fractures and vertebral fractures, cause disabilities and significant quality of life deterioration. Standard treatment of osteoporosis, based on pharmacotherapy does still not yield adequate results, and the problem of osteoporosis remains incompletely solved. Additionally, adverse drug events and fractures after long-termed pharmacotherapy pose additional challenges within designing a proper therapy regimen. Improved clinical approach and new synergistic treatment modalities are consequently still needed. The rationale of the presented study was accordingly, to expand our preclinical animal study on human patients with osteoporosis, based on positive effects on bones observed in animals with osteopenia treated with PMA-zeolite. We specifically monitored effects of PMA-zeolite on the bone quality parameters, fracture risk and quality of life in a cohort of initially recruited 100 osteoporosis patients during a follow-up period of 5 years within a randomized, placebo-controlled and double blinded clinical study (TOP study). Obtained results provide evidence on the PMA-zeolite positive effects on the bone strength of osteoporotic patients as the risk of fractures was significantly decreased in PMA-zeolite-treated patients with respect to time before entering the study (p= 0.002). Statistical evidence point also to positive bone changes in the 5-years TOP study course as evidenced through osteocalcin and beta-cross laps values showing a prevalence of the bone-formation process (p<0.05). BMD values were not significantly affected after the 5-years follow-up in PMA-zeolite-treated patients in comparison with the Placebo group. Results support the initial expectations based on our previously published preclinical studies on clinoptilolite product PMA-zeolite in animals that could be a new therapeutic option in osteoporosis patients.